KETERAMPILAN SIKAP TOLERANSI ANAK USIA 5-6 TAHUN - Lestari, Shinta; Muslihin, Heri Yusuf; Elan, Elan (JURNAL PAUD AGAPEDIA, 2020)
Tolerance in early childhood is clearly stated in STPPA (Standard for the Level of Achievement of ChildDevelopment). STPPA refers to the child's development in relation to the process of knowing and learning abouttolerance contained in the aspect score Religion and Morals (NAM) and Social-Emotional. In the 5-6 years agegroup or kindergarten, children have started to recognize the religion that is embraced, do worship , behavehonestly and are helpful, polite, respect, sportsmanship, etc., maintain personal hygiene and the environment,know the religious holidays, and respect (tolerance) of other people's religions. This study aims to describe howhabituation in the implementation of religious tolerance, describing the role of classroom teachers in carryingout religious tolerance development. This research is a descriptive qualitative approach and uses the method ofliterature study. The source of the data obtained is the study of literature that is from books, journals orscientific articles, dictionaries, and reports of research results without researchers going into the field directly.The results of this study are categorized into 2 (two) components, namely (1) habituation patterns, and (2)teacher roles.Toleransi pada anak usia dini dinyatakan secara jelas dalam STPPA (Standar Tingkat Pencapaian PerkembanganAnak). Mengacu pada STPPA tersebut, perkembangan anak dalam kaitannya dengan proses mengenal danbelajar tentang toleransi terdapat dalam aspek Nilai Agama dan Moral (NAM) dan Sosial-Emosional. Padakelompok usia 5-6 tahun atau TK Besar, anak sudah mulai mengenal agama yang dianut, mengerjakan ibadah,berperilaku jujur dan penolong, sopan, hormat, sportif, dan sebagainya, menjaga kebersihan diri danlingkungan, mengetahui hari besar agama, dan menghormati (toleransi) terhadap agama orang lain. Penelitianini bertujuan untuk mendeskripsikan bagaimana pembiasaan dalam implementasi toleransi beragama,mendeskripsikan peran guru kelas dalam melaksanaan pembinaan toleransi beragama. Penelitian ini merupakanpenelitian dengan pendekatan kualitatif deskriptif dan menggunakan metode studi literatur. Sumber data yangdiperoleh merupakan studi kepustakaan yakni dari buku, jurnal atau artikel ilmiah, kamus, dan laporan hasilpenelitian tanpa peneliti terjun ke lapangan secara langsung. Hasil dari penelitian ini dikategorikan ke dalam 2(dua) komponen yaitu (1) pola pembiasaan, dan (2) peran guru.